Future of legal gender: survey and interview data, 2018-2022 - Cooper, Davina (UK Data Service, 2022)
This dataset consists of 126 semi-structured (including 5 unstructured interviews) and a public survey to explore current understandings of legal sex/gender and attitudes towards its decertification. Decertification is used in this project to mean that people would no longer have a legal sex or gender (birth certificates, for instance, would no longer register a baby’s sex). Interviews were mostly conducted in-person prior to covid. After March 2020, they were undertaken via online platforms. The transcripts include interviews with a wide range of stakeholders exploring the implications of reform to legal sex and gender certification. Interviews also addressed organisations’ current practice in relation to the use of sex and gender categories, their response to gender identities such as agender and nonbinary, the challenges that innovation in this area face, and the question of how an identity-based approach to gender could combine with one attentive to structural gender inequalities. Predominantly semi-structured interviews were conducted with 1) Members of different publics using tailored interview methods to explore continuity, change and disruption in understandings and interpretations of gender (and its relationship to sex) across social and legal contexts; 2) public bodies, service providers, NGOs, regulatory bodies, religious communities, trade unions, legislative drafters, academics, and others working in related fields. A number of interviews were carried out for this research project that have not been archived. This is for several reasons, including in a few cases technological failure. However, one recurrent reason for non-archiving relates to the inability of organisational interviews to be sufficiently anonymised and the currently contentious nature of gender/ sex law reform discussions. In some cases, despite giving initial permission to archive when the interview was carried out, interviewees subsequently requested that their interview not be archived. The dataset also consists of a survey which explores wider public perceptions of reforming legal sex and gender. The ‘Attitudes to Gender’ survey was conducted as part of the ‘implications for the wider public’ strand of the Future of Legal Gender research project and focused on asking questions to gain a better understanding of what legal sex and gender status means for people, and whether it matters to individuals in their everyday lives. The survey ran from October to December 2018 in partial overlap with the UK Government’s public consultation on potential reform of the Gender Recognition Act 2004 (GRA) in England and Wales. We chose to develop the survey questionnaire ourselves rather than use pre-existing measures so we could ensure the survey mapped well onto the overall aims and objectives of the project. Sampling was opportunistic. We received 3101 usable responses to the survey. Some demographic data was collected and analysed (e.g. age, class, ethnicity, sexual preference, religion) but removed from this SSPS data set for anonymity purposes. Feminist activists and scholars have long questioned the idea that gender is anchored in natural biological distinctions, arguing instead that concepts of masculine and feminine, and what it means to be a woman or man, are socially generated. More recently, some transgender and intersex activists and scholars have developed these claims further, arguing that people's gender identities should not be restricted to the sex formally recorded at birth. As many people seek to live in ways that do not correspond to stereotypical notions of their gender or otherwise diverge from the sex and gender assigned them, law in different jurisdictions has responded. Gender-neutral laws, procedures for gender transitioning, and legal decisions recognising the possibility of nonbinary gender identities unsettle traditional legal regimes based on two, biologically fixed, socially differentiated genders. Yet, while reform initiatives internationally gain momentum, they tend to be limited in two key respects: first, they typically adopt an ad hoc or incremental approach to legal gender identity structures; second, they focus on legal accommodation of gender minorities within existing classificatory structures rather than more general reform. Legal and policy developments, the gender activism surrounding them (with all its internal disagreements, including over the meaning of biological sex), and the rapid upsurge of wider interest and concern about how to regulate and recognise gender identity have brought a more fundamental question to the surface: should sex remain a legal status assigned at birth; and what would be the implications of reforming this? Our project addressed this question, focusing on the legal jurisdiction of England & Wales, but drawing also on developments in Scotland and overseas. Research was organised into three consecutive work packages. The first drew on international developments and activist arguments to outline possible options for reform (for instance, birth certificates with more than two sex or gender options; allowing people to choose a legal gender on maturity; or modes of regulation that approach gender and sex in ways that are more akin to the legal treatment of sexual orientation and race which are not formal statuses in English law while still constituting protected equality grounds). The second work package focused on “decertification” as one specific reform proposal. It explored what decertification would mean: for gender-differentiated provision, such as single-sex schools, domestic violence shelters, and women's groups; for diverse equality agendas; and for how gender and sex are codified in law. This second work package also explored public attitudes to reform, and what this can tell us about the significance of legal gender in everyday life. The final work package drew the research together to understand key points of disagreement and tension regarding decertification as a law reform proposal in a British context. In this work package, we also produced a series of prototypes exploring legislative principles for decertification law reform. Decertification – the dismantling of legal sex status - involves removing sex from birth certificates so people no longer have a legal sex or (corresponding) gender status. It also entails other changes to regulatory laws that rely on sex and gender-specific terms. Adopting a multi-methods approach, research data included a public survey, online documentary materials, and interviews with NGOs, policymakers, equality specialists, trade unions, legislative drafters, and members of different publics. Through meetings, workshops and the prototyping of legislative principles, the project actively engaged stakeholders in shaping and discussing research questions, analyses, and the possible legal form that decertification could take. Research findings, analysis and conclusions are disseminated through special issues (in refereed journals), other refereed journal articles, our website, blog posts, presentations, and social and mainstream media. A detailed public report was produced at the end of the project, Cooper, D., Emerton, R., Grabham, E., Newman, H.J.H., Peel., E., Renz, F. & Smith, J. (2022) Abolishing legal sex status: The challenge and consequences of gender related law reform. Future of Legal Gender Project. Final Report. King’s College London, UK.